(untitled) - Benton, W. C. (Boston, 2010)
Preface Part 1: Introduction to Purchasing and Supply Management Chapter 1: Purchasing and Supply Management Chapter 2: Purchasing Decisions and Business Strategy Chapter 3: The Legal Aspects of Purchasing Part 2: Materials Management Chapter 4: Materials Management Chapter 5: Inventory Management Chapter 6: Just-In-Time (Lean) Purchasing Chapter 7: Purchasing Procedures, E-Purchasing, and Systems Contracting Part 3: Fundamentals of Purchasing and Supply Management Chapter 8: Supplier Selection and Evaluation Chapter 9: Strategic Outsourcing Chapter 10: Global Sourcing Chapter 11: Purchasing, Supply Partnerships, and Supply Chain Power Chapter 12: Total Quality Management (TQM) and Purchasing Part 4: Price/Cost Analysis and Negotiation Strategies Chapter 13: Price Determination Chapter 14: Bargaining and Negotiations Part 5: Special Purchasing Application Chapter 15: Purchasing Transportation Services Chapter 16: Equipment Acquisition and Disposal Chapter 17: Healthcare Purchasing and Supply Management Chapter 18: Procuring Professional Services
Keywords: Business logistics,Cung ứng kinh doanh